TEH HIJAU UNTUK OBESITAS: LITERATUR REVIEW - Safitri, Dini; Utami, Nurul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: According to the World Health Organization (WHO), obesity is one of the main global health problems and continues to increase, including in Indonesia. This research aims to examine the impact of green tea consumption on obesity by analyzing 20 journals published in Indonesia. Green tea contains bioactive compounds such as catechins that are believed to increase fat oxidation and thermogenesis, making it a promising natural intervention for weight management. In this review, each journal is analyzed based on research design, methodology, sample size, measuring tools, and main findings. The results of the analysis showed that green tea consumption consistently correlated with significant weight loss, reduced body fat, and improvements in metabolic health parameters such as lipid profiles and blood pressure. Most studies use experimental and quasi-experimental designs, with sample sizes varying from children to older adults. This research shows that green tea can be an important part of obesity management strategies in Indonesia. This study concluded that green tea has great potential as a dietary intervention for weight loss and improving metabolic health in different populations. Further studies are needed to understand the long-term effects and mechanisms underlying these benefits of green tea.Keywords: Green tea, obesity, weight loss, Indonesia, weight management, metabolic health.